Impact of Estrus Response and Pregnancy Rate of Two Cows That are Injected with Prostaglandin F2α Hormone in the System Maintenance is Different to Livestock Farming - Siregar, Nur Asyiah; Umar, Sayed; Handarini, Ristika (Randwick International of Social Science Journal, 2024)
Livestock farming is an effort to breed livestock to obtain benefits or results in the form of products and income. The success of a livestock business depends on three elements commonly referred to as the production triangle, namely seeds, feed, and management. In addition, the techno-socioeconomic characteristics of livestock farmers greatly influence the development of livestock businesses and will later affect the income of livestock farmers. The aim of the research was to examine the injection of the prostaglandin F2α hormone on the estrus response and pregnancy in Ongole crossbreed and Simental crossbreed cows reared using intensive and semi-intensive rearing systems. The data obtained will be analyzed using analysis of variance (ANOVA) and if there is a real effect, continue with further testing with Duncan's Multiple Range Test. The results of research on the percentage of estrus after the first and second injection of the prostaglandin hormone can be seen in the table. The highest percentage of estrus was in the S1P2 treatment with a percentage value of 80% and the lowest percentage value was in the S2P1 and S2P2 treatments with a percentage value of 40%. The percentage of estrus after the second injection, the percentage value for all treatments increased and the percentage of estrus was highest in the S1P2 treatment with a value of 100%. The average value of onset of estrus after the second injection of the PGF2α hormone was lower than the first injection. The longest duration of estrus in the treatment after the first PGF2α hormone injection was in the S1P2 treatment with an average of 24.75 hours, while the longest duration of estrus in the treatment after the second PGF2α hormone injection was in the S2P1 treatment with an average of 25 hours. PO cattle and Simental crossbreeds injected with PGF2α gave no different estrous responses. Intensive and semi-intensive rearing systems provide no different estrous responses. Raising PO cows using a semi-intensive rearing system injected with PGF2α provides an estrous response and high pregnancy rates (60), to be one of techniques to breed cattle of PO cow and have good impact to the success of a livestock business